The Ongoing Study of the Chemistry of the Marine Inhabitants of The Ramsar Site of Port Royal, Jamaica - Gallimore, Winklet Authrine (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
Research efforts to examine the chemistry of marine organisms collected from the Ramsar site of Port Royal, Jamaica, has led to the isolation of a range of compounds as diverse as the species from which they were derived. Six sponges, two algal species, one ascidian and one soft coral collected from the mangrove area and the shallow coastal reefs were studied to yield compounds including steroids, aromatic compounds and terpenoids.